Indentation Pop‐in Behavior of CoCrFeNiAlx High‐Entropy Alloy. Issue 11 (7th July 2022) - Meng, Lu; Xiao, Gesheng; Cui, Weiling; Shu, Xuefeng
Abstract : Indentation pop‐in behavior of CoCrFeNiAl0.1, CoCrFeNiAl0.3, and CoCrFeNiAl0.6 high‐entropy alloys (HEAs) at different loading rates is investigated using instrumental nanoindentation. Experimental results show that the increase in either loading rate or the aluminum atomic content (Al x ) of the alloy all have a reducing effect on the pop‐in behavior on the load–displacement curve. Meanwhile, both conditions exert a lagging effect on the triggered depth of the first pop‐in event and significantly affect the bursting width. The first pop‐in event is characterized using the previous phenomenological model and the effects of loading rate and Al x are quantitatively analyzed through combining the elastic deformation energy prior to the first pop‐in and the energy dissipation during the indentation process. In addition, the activation volumes for pop‐in event are evaluated to be about 4–13 Ω much higher than that in pure metal, revealing the multiatom‐coordinated migration process in HEAs. Abstract : Nanoindentation tests on high‐entropy alloys with different Al contents reveal that Al atoms can act as solute atoms to directly affect indentation pop‐in behavior. Then, the effects of Al content and loading rate on the occurrence depth and bursting width of the first pop‐in event of HEAs are quantified by combining the phenomenological model characterization and elastic deformation energy.